Prove that (AB)^-1 = B^-1 A^-1

This problem can be solved in 8 steps:

1. Let AB = C

2. A-1AB = A-1C

3. IB = A-1C as the identity matrix I = A-1A

4. B-1B = B-1A-1C premultiply both sides by B-1

5. I = B-1A-1C as B-1B = I, the identity matrix

6. C-1=B-1A-1CC-1 post multiple both sides by C-1

7. C-1=B-1A-1 as CC-1 = I, the identity matrix

8. (AB)-1=B-1A-1

Related Further Mathematics A Level answers

All answers ▸

The cubic equation 27(z^3) + k(z^2) + 4 = 0 has roots α, β and γ. In the case where β=γ, find the roots of the equation and determine the value of k


Give the general solution to (d2y/dx2) - 2dy/dx -3y = 2sinx


Take quadratic equation x^2-6x+14=0 and its solutions a and b. What is a/b+b/a?


What is De Moivre's theorem?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences